2018
DOI: 10.1002/jbt.22191
|View full text |Cite
|
Sign up to set email alerts
|

Novel amides of 1,1‐bis‐(carboxymethylthio)‐1‐arylethanes: Synthesis, characterization, acetylcholinesterase, butyrylcholinesterase, and carbonic anhydrase inhibitory properties

Abstract: The thiolation reaction was carried out in a benzene solution at 80°C and p-substituted ketones and mercaptoacetic acid in a molar ratio (1:4) of in the presence of a catalytic amount of toluene sulfonic acids. The enzyme inhibition activities of the novel amides of 1,1-bis-(carboxymethylthio)-1-arylethanes derivatives were investigated. These novel amides of 1,1-bis-(carboxymethylthio)-1-arylethanes derivatives showed good inhibitory action against acetylcholinesterase (AChE) butyrylcholinesterase (BChE), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 56 publications
(100 reference statements)
1
25
0
Order By: Relevance
“…In addition, increased AChE and BChE enzyme activities are associated with impairment of cholinergic neurons . These enzymes can be found in central nervous system, erythrocytes, brain, heart, liver, kidney, pancreas, and lung . Similar studies are found in literature.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, increased AChE and BChE enzyme activities are associated with impairment of cholinergic neurons . These enzymes can be found in central nervous system, erythrocytes, brain, heart, liver, kidney, pancreas, and lung . Similar studies are found in literature.…”
Section: Discussionsupporting
confidence: 83%
“…Butyrylcholinesterase (BChE) and acetylcholinesterase (AChE) are significant forms of cholinesterases in mammalian. They are characterized by very high concentrations in the placental tissue, brain, muscle, nerve cells, and erythrocytes . The α‐glycosidase (α‐Gly) enzyme breaks glycosidic chain bonds in complex carbohydrate and releases absorbable monosaccharide molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The α‐glycosidase enzyme has been recorded to be of particular concern in pharmaceutical studies, since the inhibitory activity of this metabolic enzyme can perform lagged glucose absorption and the liberation of the glucose molecule from complex carbohydrate compounds, resulting in decreased postprandial plasma blood glucose and suppression of postprandial hyperglycemia . α‐Glycosidase inhibitor (AGI) compounds have been considered as therapeutic agents for the treatment of symptoms such as hyperglycemia, obesity, and type II non‐insulin–dependent diabetes milletus (DM2).…”
Section: Introductionmentioning
confidence: 99%
“…AZA is used as a control for CA inhibitors (CAIs) and for the medical treatment of glaucoma, altitude sickness, epileptic seizure, dural ectasia, and idiopathic intracranial hypertension . In addition, CA II was chosen because of its antiglaucoma effects, while CA I was chosen because its dispensation in the gastrointestinal tract and in the blood is one of the main functions of such pharmacological agents . CAIs have been utilized to treat a variety of diseases, including glaucoma, epilepsy and altitude sickness.…”
Section: Discussionmentioning
confidence: 99%